2010
DOI: 10.1152/ajpregu.00781.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin as a regulator of cardiac function and postprandial gastrointestinal blood flow in rainbow trout (Oncorhynchus mykiss)

Abstract: We have studied the potential role of CCK as a regulator/modulator of the postprandial increase in gastrointestinal blood flow. Rainbow trout (Oncorhynchus mykiss) were instrumented with pulsed Doppler flow probes to measure the effects of CCK on cardiac output and gastrointestinal blood flow. Furthermore, vascular preparations were used to study the direct effects of CCK on the vessels. In addition, we used in situ perfused hearts to further study the effects of CCK on the cardiovascular system. When the sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Indeed, when reviewing the current literature on cardioventilatory data for similar sized rainbow trout at ∼10°C it is obvious that our values are considerably lower than most previous values. For example, the mean heart rate of the untreated control group on day 5 in the present study (30.2±2.4 beat min −1 ) is 13–26 beats min −1 lower than most values reported in the literature using appropriate techniques and a post-surgical recovery time of at least 24 h [15], [21], [33]–[35]. The already remarkably low heart and ventilation rates were further reduced after an administration of buprenorphine, resulting in values 21.9±2.6 beat min −1 and 40.0±1.7 breaths min −1 , respectively, which to our knowledge, are the lowest values ever reported for rainbow trout at 10°C.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Indeed, when reviewing the current literature on cardioventilatory data for similar sized rainbow trout at ∼10°C it is obvious that our values are considerably lower than most previous values. For example, the mean heart rate of the untreated control group on day 5 in the present study (30.2±2.4 beat min −1 ) is 13–26 beats min −1 lower than most values reported in the literature using appropriate techniques and a post-surgical recovery time of at least 24 h [15], [21], [33]–[35]. The already remarkably low heart and ventilation rates were further reduced after an administration of buprenorphine, resulting in values 21.9±2.6 beat min −1 and 40.0±1.7 breaths min −1 , respectively, which to our knowledge, are the lowest values ever reported for rainbow trout at 10°C.…”
Section: Discussioncontrasting
confidence: 66%
“…This procedure was chosen to mimic a surgical technique that can be considered rather invasive and that is routinely used in rainbow trout, e.g. to access the coeliacomesenteric artery and other organs in the abdominal cavity [19][21]. The surgery took around 15 min, and including anaesthesia and post-operative wake up the entire procedure took around 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It could also indicate that there is a change in the tonus of the smooth musculature of the gastrointestinal tract leading to a change in the transmural pressure of the vasculature. This is also unlikely considering that there is a considerable vasorelaxation in isolated gastrointestinal vessels when adding atropine (Seth et al, 2010). The most likely explanation is that the effect instead represents a pharmacological artifact.…”
Section: Regulation Of Nutrient-induced Intestinal Hyperemiamentioning
confidence: 99%
“…The correct dosage was obtained using in-situ perfused hearts (N4) as previously described by Seth et al (Seth et al, 2010) and the concentration of TTX in the perfusate was increased in a stepwise manor until a change in the contractility of the heart was noticed. Additional in vivo trials on anaesthetized fish (N4) were also conducted.…”
Section: In Situ Measurement Of Cardiovascular Variables In Untreatedmentioning
confidence: 99%
“…The potential for these peptides to mediate the postprandial hyperemia is based on the fact that they typically produce vasodilation in the intestine. However, with few exceptions [e.g., CCK in rainbow trout (435) and neurotensin in the python (459)], the concentration of the peptide that must be infused in the intestinal arterial supply to elicit vasodilation far exceeds the levels achieved in intestinal venous blood postprandially (143,146,435). While this is also the case for VIP (143), studies have demonstrated that administration of a VIP blocking antibody reduces the jejunal blood flow response to micellar oleic acid by approximately 70% (412) (Fig.…”
Section: Small Intestine Functional Hyperemia (Postprandial Hyperemia)mentioning
confidence: 99%